2018
DOI: 10.3390/en11081950
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Injection Strategy of Branched-Preformed Particle Gel/Polymer/Surfactant for Enhanced Oil Recovery after Polymer Flooding in Heterogeneous Reservoirs

Abstract: Abstract:The heterogeneous phase combination flooding (HPCF) system which is composed of a branched-preformed particle gel (B-PPG), polymer, and surfactant has been proposed to enhance oil recovery after polymer flooding in heterogeneous reservoirs by mobility control and reducing oil-water interfacial tension. However, the high cost of chemicals can make this process economically challenging in an era of low oil prices. Thus, in an era of low oil prices, it is becoming even more essential to optimize the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…They concluded that sequential injection of branched preformed particle gel and hydrolyzed polyacrylamide would provide higher oil recovery factor as the combination of these chemical agents can provide an adjustable fluid mobilization in different permeable zones due to its deforming and blocking agents. Moreover, hydrolyzed polyacrylamide can increase the branched preformed particle gel sustained effect, which can help to increase the resistance factor [41].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that sequential injection of branched preformed particle gel and hydrolyzed polyacrylamide would provide higher oil recovery factor as the combination of these chemical agents can provide an adjustable fluid mobilization in different permeable zones due to its deforming and blocking agents. Moreover, hydrolyzed polyacrylamide can increase the branched preformed particle gel sustained effect, which can help to increase the resistance factor [41].…”
Section: Introductionmentioning
confidence: 99%
“…Selection of surfactants for foaming application in EOR, CO 2 sequestration, hydraulic fracturing, and other upstream applications is a challenging task [17][18][19][20][21][22][23][24][25]. A surfactant for foaming applications should be generally thermally stable, compatible with reservoir brine and other chemicals, have lower adsorption on reservoir rock, have high foamability and foam stability, and should be economically viable [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The high and low permeability sand packs were used in combination to simulate the reservoir heterogeneity. The high and low permeability sand packs were prepared as follows [36,37]: The sand packs were positioned vertically and filled with formation brine, then fresh quartz sand with different mesh sizes were added into the sand packs and packed by vibration.…”
Section: Parallel Sand Pack Flooding Testmentioning
confidence: 99%
“…Figure 3 shows the schematic diagram of the experimental setup for the plate sand pack flooding. The experimental setup was composed of four parts: ISCO pump (Teledyne ISCO company, Lincoln, Lincoln, Nebraska, USA), sand pack model, Inductance-Capacitance-Resistance (LCR) digital bridge (Changzhou Tonghui Electronic Co., Ltd, Changzhou, China), and the oil-water saturation acquisition control system [37]. The oil-water saturation can be obtained by measuring the resistivity.…”
Section: Parallel Sand Pack Flooding Testmentioning
confidence: 99%
See 1 more Smart Citation